Penggunaan Video Pembelajaran Pjok Melalui Media Sosial Youtube Pada Siswa Kelas VIII SMP Negeri 2 Karawang Barat di Masa Pandemi Covid-19 - Paulus Situmorang; Nana Nasution; Rolly Afrinaldi (Peneliti.net, 2021)
This study aims to find out how to use Pjok learning videos through YouTube social media in class VIII at SMPN 2 Karawang Barat. The subjects in this study were the vice principal of the curriculum, physical education teacher and 4 students of class VIII A of SMPN 2 Karawang Barat. With the use of qualitative methods then interviews and documentation as data collection techniques and qualitative descriptive analysis techniques in this study are expected to provide maximum results. The findings of this study indicate that the learning process at SMPN 2 Karawang Barat is carried out online through various social media such as whatsapp, zoom meet, google meet, google classroom and other social media such as youtube. Due to the PJOK learning process, which was supposed to carry out various activities in the field, it was hampered due to the COVID-19 pandemic. In the learning process, the teacher gives direction to students in the form of sending a web link through the class whatsapp group. So that students can learn materials in the form of existing PJOK learning videos. In the material there is text combined with moving images so that students can understand the contents of the learning material, but teachers and students still experience obstacles during the PJOK learning process due to poor internet access and not all children have communication tools (mobile phones) to communicate. carry out learning activities. Therefore, there are still many students who find it difficult to understand the content of the material that has been given by the teacher through learning videos.